2022
DOI: 10.3389/fpubh.2021.811345
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Associated Factors of Depressive Symptoms Among Medical Students in Bangladesh During the COVID-19 Pandemic: A Cross-Sectional Pilot Study

Abstract: BackgroundWhilst very limited studies have demonstrated a correlation between the COVID-19 pandemic and depressive symptoms amongst Bangladeshi medical students, the prevalence and associated factors of depressive symptoms as measured by the Patient Health Questionnaire (PHQ-9) remains widely unknown.ObjectiveThe study aimed to investigate the prevalence and factors associated with depression symptoms among Bangladeshi medical students during the COVID-19 pandemic lockdown period.MethodIn this web-based cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Slovak students also reported more depression than anxiety, which is in line with the results revealed by Hajduk et al ( 57 ). In comparison, a similar prevalence was observed among Indian doctoral students (26.7%) ( 86 ), Chinese students (15.8%) ( 87 ), and Korean students (14%) ( 88 ), while a higher prevalence was observed among students from Germany (37%) ( 89 ), Bangladesh (48.8%) ( 90 ), and Malaysia (33.8%) ( 91 ). The mean score was 6.34 for Czech students and 5.77 for Slovak students, indicating mild depressive symptoms.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Slovak students also reported more depression than anxiety, which is in line with the results revealed by Hajduk et al ( 57 ). In comparison, a similar prevalence was observed among Indian doctoral students (26.7%) ( 86 ), Chinese students (15.8%) ( 87 ), and Korean students (14%) ( 88 ), while a higher prevalence was observed among students from Germany (37%) ( 89 ), Bangladesh (48.8%) ( 90 ), and Malaysia (33.8%) ( 91 ). The mean score was 6.34 for Czech students and 5.77 for Slovak students, indicating mild depressive symptoms.…”
Section: Discussionmentioning
confidence: 58%
“…Based on the mean score, mild depressive symptoms were also reported by German (6.77) and Chinese (6.99) students ( 85 ). A higher mean score reported Bangladeshi students (9.5) ( 90 ), Polish students (11.3) ( 92 ), and Greek students (9.36) ( 93 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies provided evidence regarding the poor mental health condition of Bangladeshi university students ( 14 , 15 ). Additionally, Bangladeshi medical students show a very high frequency of depression symptoms, with the COVID-19 pandemic underway, the concerning prevalence and associated variables of depression point to the necessity for follow-up psychological interventions targeted at medical students ( 16 ). Safa et al ( 17 ) found that 27.3% of medical students have mild anxiety, 26.8% have moderate anxiety, and 11.8% have severe anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…A recent pilot study in Bangladesh similarly identified a very high prevalence of depression symptoms among Bangladeshi medical students. 26 Our study has several strengths. We had a large survey sample size of more than 2700 participants with an excellent response rate (90%) that surveyed multiple disciplines and different job roles in four major hospitals in Bangladesh.…”
Section: Discussionmentioning
confidence: 96%
“…25 Female gender, increased social media use, low levels of optimism and sleeping problems increased the risk of depression in trainee medical students during the pandemic in Bangladesh. 26 There has however been limited large-scale work exploring the impact of COVID-19 on anxiety, depression and burnout in healthcare workers in Bangladesh. The aim of this study was therefore to explore levels of burnout, anxiety and depression in doctors and nurses within Bangladesh during the COVID-19 pandemic.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%